Role of intranasal fluticasone furoate spray in modifying quality of life of children with adenoid hypertrophy (Bangladesh Journal of Otorhinolaryngology, 2020)
Introduction: Symptoms of adenoid hypertrophy is commonly seen among the pediatric age group. Since the surgical approach for this on immunity is controversial, the study was planned out to appraise the outcome of intranasal Fluticasone Furoate spray use.Objective:To find out the efficacy of Fluticasone Furoate nasal spray in reducing clinical symptoms due to enlarged adenoid.Methods: The prospective observational study was conducted in the Rangpur Medical College Hospital between April 2017 to August 2017 among 64 patients aged 4-15 years. Improvement on clinical symptoms was assessed by the structured OSA-18 questionnaire.Results: At the end of 4 weeks, statistically significant improvement (p < 0.001) was observed in nearly all the domains of among the 64 participants. The average total score showed improvement from 60.95 to 46.37.Conclusion:The use of fluticasone furoate nasal spray considered to be useful in reducing clinical symptoms of adenoid hypertrophy among children.Bangladesh J Otorhinolaryngol; April 2018; 24(1): 22-28